2019
DOI: 10.1039/c9cc03977e
|View full text |Cite
|
Sign up to set email alerts
|

Sensing and imaging of mitochondrial viscosity in living cells using a red fluorescent probe with a long lifetime

Abstract: A red mitochondria-targeting probe (Mito-V) with a long lifetime for viscosity assay has been successfully applied to monitor the viscosity changes in the courses of apoptosis, inflammation, hyperglycemia and antifungal medication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 132 publications
(47 citation statements)
references
References 36 publications
2
44
0
Order By: Relevance
“…Although conventional dyes (e.g., mitochondria-tracker and lysosometracker probes) report the morphology of mitochondria and lysosomes 3 , they are insensitive to viscosity and therefore do not track the dynamic changes of an organelle's internal environment. Recently developed viscosity probes 22 can realize the imaging of the viscosity of a single organelle by using fluorescent probe with rotatable C sp 2 -C sp 2 bond [23][24][25] . In Coupa, there is also C 2p 2 -C sp 2 bond in its molecule skeleton, this may provide Coupa also the fluorescent viscosity sensing ability.…”
Section: Resultsmentioning
confidence: 99%
“…Although conventional dyes (e.g., mitochondria-tracker and lysosometracker probes) report the morphology of mitochondria and lysosomes 3 , they are insensitive to viscosity and therefore do not track the dynamic changes of an organelle's internal environment. Recently developed viscosity probes 22 can realize the imaging of the viscosity of a single organelle by using fluorescent probe with rotatable C sp 2 -C sp 2 bond [23][24][25] . In Coupa, there is also C 2p 2 -C sp 2 bond in its molecule skeleton, this may provide Coupa also the fluorescent viscosity sensing ability.…”
Section: Resultsmentioning
confidence: 99%
“…Ma and colleagues synthesized a red fluorescent probe 12 with long lifetime, achieving the visualization of mitochondrial viscosity in live cells [39] . Probe 12 was fabricated by attaching cationic hemicyanine to aniline through a rotatable C−C bond.…”
Section: Small Molecular Fluorescent Probes For Viscositymentioning
confidence: 99%
“…(C) Fluorescence imaging of intracellular viscosity under different conditions with probe 12 . Copyright 2019, Royal Society of Chemistry [39] . (D) Fluorescence imaging of viscosity distribution in liver slice tissues with probe 13 .…”
Section: Small Molecular Fluorescent Probes For Viscositymentioning
confidence: 99%
“…It has been found that micro-viscosity varies from 1 to 400 cP in cells. [147][148][149] Abnormalities in intracellular viscosity is associated with severe diseases, such as cancer, [150] AD, [151,152] diabetes, [153] HD and ALS, [154] Leigh's syndrome, [155] and atherosclerosis. [156] After examination of hemorheological parameters, it was found that vascular perturbations in AD patients result from hemorheological derangements, such as increased whole blood viscosity, decreased red cell deformability, increased red cell aggregation, and increased fibrinogen.…”
Section: Viscositymentioning
confidence: 99%